'He is telling us fairy tales': parental anxiety and wartime childhood in Life is Beautiful, The Boy in the Striped Pajamas and Fairy Tales from Auschwitz. Issue 1 (2nd January 2018) - Gildersleeve, Jessica; Batorowicz, Beata
ABSTRACT: This essay explores the stories and lies told to children during the Holocaust, and how these operate as forms of preparation and protection within and outside the narrative. In Roberto Benigni's Life is Beautiful (1997) and Mark Herman's The Boy in the Striped Pajamas (2008) parents seek to protect children from the knowledge of war, but this prevents anxiety-preparation. In contrast, the historical document Fairy Tales from Auschwitz does not deny the horrific reality of life in the camp, but uses the fairy tale genre as a reassurance of morality and survival.